Exploring the relationship between dual diagnosis and recidivism in drug court participants - Zettler, Haley R. (Crime & delinquency, 2018)
There is limited research investigating the relationship between dual diagnosis and offender outcomes in drug court settings, specifically regarding recidivism. The current study examined the effects of dual diagnosis on recidivism following participation in one drug court in the Southwestern United States. Results provided mixed evidence surrounding the impact of dual diagnosis on recidivism outcomes. Dual diagnosis significantly increased the odds of recidivism for participants at 6 months but the effect was not significant at 12 months. These findings suggest that dual diagnosis may play a role in offender recidivism shortly after participation in drug court. In addition, some differences between dually diagnosed participants and those with only substance use diagnoses were found.